COMPARATIVE ANALYSIS OF THE PERFORMANCE OF SERIES AND PARALLEL ELECTRICAL CIRCUITS IN MINIATURE HOUSE MEDIA FOR BASIC SCIENCE LEARNING - Raskita Mega Wati Br.Pinem; Siti Aisyah; Nurul Hasanah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the comparative performance of series and parallel electrical circuits through a practical activity using a miniature house as a learning tool for basic science. The practical activity is designed to help students understand basic electrical concepts in a contextual and concrete manner. The tools used in this activity include a small flashlight, batteries, a mini switch, wires, insulation, and supporting materials such as cardboard to design the miniature house. Students build two types of circuits—series and parallel—and then observe the characteristics of each, such as the number of lights lit, the brightness of the light, and the impact of removing one component in the system. The observations indicate that the series circuit has a high degree of interdependence between components, where the failure of one light causes the entire system to shut down. Conversely, the parallel circuit exhibits greater stability, as each light remains lit even if one is removed, providing brighter lighting. This practical demonstrates that the use of a miniature house not only engages students but is also effective in explaining basic electrical concepts through hands-on experience. Therefore, the application of a simple experiment-based learning model like this is recommended to improve students' understanding of basic science, particularly electricity.